A Comparison of hs-CRP Levels in New Diabetes Groups Diagnosed Based on FPG, 2-hPG, or HbA1c Criteria. (28th December 2015) - Tutuncu, Yildiz; Satman, Ilhan; Celik, Selda; Dinccag, Nevin; Karsidag, Kubilay; Telci, Aysegul; Genc, Sema; Issever, Halim; Tuomilehto, Jaakko; Omer, Beyhan
Abstract : Fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c) have been used to diagnose new-onset diabetes mellitus (DM) in order to simplify the diagnostic tests compared with the 2-hour oral glucose tolerance test (OGTT; 2-hPG). We aimed to identify optimal cut-off points of high sensitive C-reactive protein (hs-CRP) in new-onset DM people based on FPG, 2-hPG, or HbA1c methods. Data derived from recent population-based survey in Turkey (TURDEP-II). The study included 26, 499 adult people (63% women, response rate 85%). The mean serum concentration of hs-CRP in women was higher than in men (p < 0.001 ). The people with new-onset DM based on HbA1c had higher mean hs-CRP level than FPG based and 2-hPG based DM cases. In HbA1c, 2-hPG, and FPG based new-onset DM people, cut-off levels of hs-CRP in women were 2.9, 2.1, and 2.5 mg/L [27.5, 19.7, and 23.5 nmol/L] and corresponding values in men were 2.0, 1.8, and 1.8 mg/L (19.0, 16.9, and 16.9 nmol/L), respectively (sensitivity 60–65% and specificity 54–64%). Our results revealed that hs-CRP may not further strengthen the diagnosis of new-onset DM. Nevertheless, the highest hs-CRP level observed in new-onset DM people diagnosed with HbA1c criterion supports the general assumption that this method might recognize people in more advanced diabetic stage compared with other diagnostic methods.